2012
DOI: 10.1089/aid.2011.0101
|View full text |Cite
|
Sign up to set email alerts
|

Occluding the Mannose Moieties on Human Immunodeficiency Virus Type 1 gp120 with Griffithsin Improves the Antibody Responses to Both Proteins in Mice

Abstract: To assess the influence of mannosylated glycans on the immunogenicity of human immunodeficiency virus type 1 (HIV-1) Env proteins, we immunized mice with monomeric gp120 in the presence and absence of the mannosebinding protein, griffithsin (GRFT). For comparison, other groups of mice received the nonglycosylated HIV-1 Gag protein, with and without GRFT. Coimmunization with GRFT increased the anti-gp120 IgG reactivity significantly, but had no effect on the anti-Gag response. We also investigated the IgG respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Consistent with our results, increased immunogenicity has also been observed for HIV gp120 when terminal mannose moieties, which are abundantly present on gp120 proteins expressed in mammalian cells, are removed (1). In another study, the antibody response against gp120 was shown to be enhanced by occluding the mannose moieties on gp120 with griffithsin (2). It was demonstrated that the terminal mannose moieties of the N-linked glycans of HIV gp120 induce immunosuppressive responses in dendritic cells, which correlated with DC-SIGN expression on these cells (30).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our results, increased immunogenicity has also been observed for HIV gp120 when terminal mannose moieties, which are abundantly present on gp120 proteins expressed in mammalian cells, are removed (1). In another study, the antibody response against gp120 was shown to be enhanced by occluding the mannose moieties on gp120 with griffithsin (2). It was demonstrated that the terminal mannose moieties of the N-linked glycans of HIV gp120 induce immunosuppressive responses in dendritic cells, which correlated with DC-SIGN expression on these cells (30).…”
Section: Discussionsupporting
confidence: 89%
“…However, more subtle effects of the Env-CD4 interaction on vaccine-induced immune responses in the absence of a strong adjuvant were not investigated in that study. Furthermore, others have shown that Env binding to CLRs on DCs stimulates an immunosuppressive response (66) and DC apoptosis (67), and blocking or removing the mannose moieties on Env, and thus precluding endocytosis via CLRs, enhanced Env-specific humoral responses in vivo (68, 69). Thus, uptake and presentation pathways not relying on CLRs may be relevant to Env vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…These immunosuppressive effects have all been shown to be dependent on Env interactions with mannose-binding CLRs, such as DC-SIGN and MR (Shan et al 2007;Chung et al 2012;Chen et al 2013). In line with these observations, immunization of humanized mice with Env glycoproteins where the mannose moieties were occluded or removed, thus preventing binding to CLRs and presumably circumventing this route of DC dysfunction, resulted in enhanced Env-specific Ab titers and T cell responses (Banerjee et al 2009(Banerjee et al , 2012. As mentioned above, the position and type of N-linked glycans on Env may again play a critical role in these negative effects on DC function (Shan et al 2007).…”
Section: Env-mediated Immunosuppressionmentioning
confidence: 81%